A Review of Remote Fieldwork Supervision for BCBA® Trainees by Lisa N. Britton and Matthew J. Cicoria - Sipila-Thomas, Emma S.; Brodhead, Matthew T. (Behavior analysis in practice, 2020)
In this article we review Britton and Cicoria’s ( 2019 ) Remote Fieldwork Supervision for BCBA® Trainees ( Remote Fieldwork Supervision ), published by Academic Press. We describe the key features of Remote Fieldwork Supervision and then provide a brief overview and descriptive review of each chapter and its content. Where appropriate, we also provide our critical analysis of the book’s content. We conclude with the positive recommendation that practitioners of behavior analysis and students who engage (or plan to engage) in remote supervision incorporate technology into their everyday supervisory practice, as well as that those who are interested in learning more about supervision should consider reading this book.